Development of Phytomonas lipae sp. n. (Kinetoplastea: Trypanosomatidae) in the true bug Coreus marginatus (Heteroptera: Coreidae) and insights into the evolution of life cycles in the genus Phytomonas - Frolov, Alexander O; Malysheva, Marina N; Ganyukova, Anna I; Spodareva, Viktoria V; Yurchenko, Vyacheslav; Kostygov, Alexei Y (PloS one, 2019)
Here we described a new trypanosomatid species, Phytomonas lipae, parasitizing the dock bug Coreus marginatus based on axenic culture and in vivo material. Using light and electron microscopy we characterized the development of this flagellate in the intestine, hemolymph and salivary glands of its insect host. The intestinal promastigotes of Phytomonas lipae do not divide and occur only in the anterior part of the midgut. From there they pass into hemolymph, increasing in size, and then to salivary glands, where they actively proliferate without attachment to the host's epithelium and form infective endomastigotes. We conducted molecular phylogenetic analyses based on 18s rRNA, gGAPDH and HSP83 gene sequences, of which the third marker performed the best in terms of resolving phylogenetic relationships within the genus Phytomonas. Our inference demonstrated rather early origin of the lineage comprising the new species, right after that of P. oxycareni, which represents the earliest known branch within the Phytomonas clade. This allowed us to compare the development of P. lipae and three other Phytomonas spp. in their insect hosts and reconstruct the vectorial part of the life cycle of their common ancestor.
Keywords: proteiny teplotního šoku; zvířata; střeva; Phylogeny; Protozoan Proteins; Intestines; RNA ribozomální 18S; pravděpodobnostní funkce; Heteroptera; Kinetoplastida; Animals; RNA, Ribosomal, 18S; slinné žlázy; Salivary Glands; stadia vývoje; Heat-Shock Proteins; Likelihood Functions; Life Cycle Stages; protozoální proteiny; Trypanosomatina; fylogeneze